2024
DOI: 10.1039/d3ce01177a
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of planar and planar layer-stacked CHON-containing molecules

Shitai Guo,
Kairui Xue,
Jing Huang
et al.

Abstract: This paper unveils the characteristics of planar and planar layer-stacked CHON-containing molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Very recently, we focused upon it based on the existing experimentally observed crystal packing and filled in the blank. 41,42 We constructed a data set comprising 65 planar layer-stacked molecules and confirmed that six point groups are covered therein with C s weighting the most heavily, high planarity tends to result in planar layer-stacking, and intermolecular HBs and the C�O group appear frequently to maintain the layers. 41 Still, the crystal packing of the remaining 55 molecules with lower symmetry remains unclear.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…Very recently, we focused upon it based on the existing experimentally observed crystal packing and filled in the blank. 41,42 We constructed a data set comprising 65 planar layer-stacked molecules and confirmed that six point groups are covered therein with C s weighting the most heavily, high planarity tends to result in planar layer-stacking, and intermolecular HBs and the C�O group appear frequently to maintain the layers. 41 Still, the crystal packing of the remaining 55 molecules with lower symmetry remains unclear.…”
Section: Introductionmentioning
confidence: 73%
“…Notably, molecules containing exclusively O−H bonds appear rarely, with only one sample of KECYBU02. 41 3.1. Stacking of H-free Molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations